Efficacy of Ivermectin and Combination of Eprinomectin with Fipronil against Demodicosis in Cats - Dangi, Rakesh; Mehta, Hemant Kumar; Choudhary, Nidhi Singh; Bagherwal, Rajendra Kumar; Jayraw, Anantrao K; Aich, Ranjit (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Parasitic skin diseases are important part of feline dermatology in general. Feline demodicosis is caused by Demodex cati, Demodex  gatoi and an unnamed species. The present investigation was conducted to diagnose and study the haemato-biochemical alterations  and therapeutic efficacy of ivermectin and eprinomectin with Fipronil in feline demodicosis. Clinical examinations of gross lesions  and microscopic examination of deep skin scrapings were used for diagnosis. Haematological study revealed microcytic hypochromic  anaemia, leucocytosis with neutrophilia, lymphopenia and eosinophilia in most of cats with demodicosis which improved significantly  following 28 days of treatment. No significant change in plasma AST-ALT activity was noted in cats affected with demodicosis. The  efficacy of different therapeutic regimens was assessed based on disappearance of clinical symptoms and restoration of altered haemato biochemical parameters. It was found that both the regimen were effective for treatment of demodectic cats, however, the recovery  rate was faster in group treated with spot on containing two acaricide drug eprinomectin and fipronil.
Keywords: Cat; Demodicosis; Eprinomectin; Ivermectin.